2020
DOI: 10.3389/fimmu.2020.01397
|View full text |Cite
|
Sign up to set email alerts
|

C5aR1 Activation Drives Early IFN-γ Production to Control Experimental Toxoplasma gondii Infection

Abstract: Toxoplasma gondii (T. gondii) is a parasite infecting animals and humans. In intermediate hosts, such as humans or rodents, rapidly replicating tachyzoites drive vigorous innate and adaptive immune responses resulting in bradyzoites that survive within tissue cysts. Activation of the innate immune system is critical during the early phase of infection to limit pathogen growth and to instruct parasite-specific adaptive immunity. In rodents, dendritic cells (DCs) sense T. gondii through TLR11/12, leading to IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 73 publications
(119 reference statements)
0
11
0
Order By: Relevance
“…While C3aR deficiency in BALB/c was partially protective in DDS-induced colitis, there was no significant effect observed in C57BL/6 mice ( Wende et al, 2013 ), indicating that differences between these two mice strains are important factors in these phenotypes. Given this evidence and the recently demonstrated role of C5aR signaling in systemic T. gondii infection ( Briukhovetska et al, 2020 ), it is highly likely that anaphylatoxins play an important role in promoting inflammation in the gut during T. gondii infection.…”
Section: Additional Insights and Outstanding Questionsmentioning
confidence: 93%
See 3 more Smart Citations
“…While C3aR deficiency in BALB/c was partially protective in DDS-induced colitis, there was no significant effect observed in C57BL/6 mice ( Wende et al, 2013 ), indicating that differences between these two mice strains are important factors in these phenotypes. Given this evidence and the recently demonstrated role of C5aR signaling in systemic T. gondii infection ( Briukhovetska et al, 2020 ), it is highly likely that anaphylatoxins play an important role in promoting inflammation in the gut during T. gondii infection.…”
Section: Additional Insights and Outstanding Questionsmentioning
confidence: 93%
“…These findings are consistent with an established role for locally produced C3a and C5a in regulating Th1 responses through autocrine and paracrine C3aR/C5aR receptor signaling ( Strainic et al, 2008 ; Liszewski et al, 2013 ). More recently, infection studies in C5ar1 −/− mice showed that these mice also die acutely, but with a much less dramatic phenotype or kinetic than the DKO mice ( Briukhovetska et al, 2020 ). In this study, 50 cysts of the Type II strain Me49 were injected intraperitoneally.…”
Section: Complement: Protective and Pathological Role During mentioning
confidence: 99%
See 2 more Smart Citations
“…Toxoplasma parasites can directly upregulate the complement factor B (CFB), complement component factor properdin (CFP), C3, and C5aR1 in glial cells. Since the C5a/C5aR1 axis increases interleukin 12 (IL-12) induction in splenic dendritic cells and subsequent inducible nitric oxide synthase (iNOS) expression in the brain [ 64 ], the continued overexpression of C3aR and C5aR1 in the infected brains could be probably correlated with the defense against Toxoplasma infection-induced damages in the CNS [ 63 ].…”
Section: Parasite’s Complement Regulatory and Evasion Moleculesmentioning
confidence: 99%